Non-exhaustive channel access strategy in multi-resource communication systems with non-homogeneous traffic - Melikov, AZ; Deniz, DZ (IEEE Computer Soc, 2000)
In this paper, channel access in multi-resource communication systems with non-homogeneous traffic under the condition of non-exhaustive channel allocation is investigated The mathematical model of the system is developed and a new efficiency algorithm for calculation of the system behavior is obtained. Numerical calculations for a sample system using the algorithm developed is carried out and results including the optimization of the model are obtained.
5th IEEE Symposium on Computers and Communications (ISCC 2000) -- JUL 03-06, 2000 -- JUAN LES PINS, FRANCE
Keywords: Environment; Blocking